Performance di recenti imboschimenti con quercia da sughero in ex-coltivi - Dettori, S.; Falqui, A.; Filigheddu, M. R.; Sedda, L. (iForest - Biogeosciences and Forestry, 2006)
Recently, significant forestry activities have taken place in Sardinia thanks to EU Regulation 2080/92 funds. Some 80% of the afforestated surface has been planted with holm oak and cork oak. The latter also characterizes 89% of the reforestation area. Given the funding source, plantations have been established on farmlands. Growth performances of these recent cork oak stands have been quantitatively evaluated and compared with the performances of two experimental plots. In Gallura (north-east of Sardinia), that is the traditional cork production area and still is economically the most important cork district of the island, these new cork oak plantations have an average size of 28 ha. They have been established on lands that, before plantation, were either pastures (30%) or arable lands (70%). Plantation failures are limited to 8.8% of the total (in term of mass) and seem independent of environmental factors or plantations species composition (conifers have been frequently used as secondary species). Average growth of the stem, measured above cork at collar height, is in the range 4 to 8mm/year with a mean value of 5.5mm/year. No correlation appears with either environmental conditions or species composition of the plantations. In the first experimental plot, soil management practices (natural vegetation removal vs its cutting and mulching) does not differentiate young plants growth trends. In the control subplots (no removal) stem collar diameter is 20% smaller. Localized manual hoeing around trunk base increased the diameters by 13% but reduced cork thickness by 21%. The second experimental plot allows comparisons among 27 Mediterranean proveniences of cork oak. The trial exhibits reduced genetic influence: diameters and heights growth are significantly different only among extreme groups. In conclusion, reduced growth performances of the plantations established in farmlands is due, to some extent, to the limitations inherent with private land management (constrained to costs minimization) and, on the other hand, to the generally very limited thickness of Gallura soils. Demand for good quality commercial cork is steadily raising. To sustain the request, in the short term, it would be necessary to extend financial support for plantations care, from 5 to 10 years, or even up to the first stripping (virgin cork).
The following values have no corresponding Zotero field: pub-location: Dipartimento di Economia e Sistemi arborei Universit di Sassari, via E. De Nicola 9, 07100 Sassari. publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Afforestation; Cork oak; Growth; Performance; Reg EEC 2080/92; Sardinia

Management problems in Mediterranean cork oak forests: post-fire recovery - Barberis, a; Dettori, S.; Filigheddu, M. R. (Journal of Arid Environments, 2003)
The objective of this paper is to present the results of a long-term research project carried out in north-east Sardinia, which aims to evaluate the effects of three different kinds of forest management (traditional trunk coppicing, branch pruning, and no sylvicultural practice) on the post-fire recovery of a cork oak (Quercus suber L.) stand. The most and the least effective forestry operations appeared to be traditional trunk coppicing and the branch pruning, respectively. Where traditional trunk coppicing is considered strictly necessary, the opportunity of thinning some of the new suckers should be carefully considered, as modern harvesting techniques should be combined with appropriate strategies to protect the soil from erosion.
Keywords: post-fire recovery; suckers growth